1998
DOI: 10.1046/j.1365-313x.1998.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel D6‐acyl‐group desaturase by targeted gene disruption in Physcomitrella patens

Abstract: SummaryThe moss Physcomitrella patens contains high levels of arachidonic acid. For its synthesis from linoleic acid by desaturation and elongation, novel ∆5-and ∆6-desaturases are required. To isolate one of these, PCR-based cloning was used, and resulted in the isolation of a full-length cDNA coding for a putatively new desaturase. The deduced amino acid sequence has three domains: a N-terminal segment of about 100 amino acids, with no similarity to any sequence in the data banks, followed by a cytochrome b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 185 publications
(183 citation statements)
references
References 36 publications
5
172
1
3
Order By: Relevance
“…The moss P. patens contains not only plant typical C18-fatty acids like LA or α-LeA but also γ-LeA and C20-fatty acids like AA and eicosapentaenoic acid (EPA) (Girke et al, 1998). These fatty acids may all serve as source for the formation of oxylipins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The moss P. patens contains not only plant typical C18-fatty acids like LA or α-LeA but also γ-LeA and C20-fatty acids like AA and eicosapentaenoic acid (EPA) (Girke et al, 1998). These fatty acids may all serve as source for the formation of oxylipins.…”
Section: Discussionmentioning
confidence: 99%
“…These organisms contain C18, C20, and longer chain length fatty acids (Dembitsky, 1993). In the moss Physcomitrella patens for example the main fatty acids are palmitic acid, LA and arachidonic acid (AA) (Girke et al, 1998). Certain mosses are known to emit aldehydes and their corresponding alcohols, like octenal, octenol but also hexanal and hexenal (Dembitsky, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…PP1 was targeted with a circular insertional knockout construct (7) based on a 1.2-kb HindIII fragment cloned into the unique HindIII site of pGL2 (11); in this case, an additional NcoI site was inserted into the recombinant gene to provide additional proof of targeted knockout in Southern analysis. PP2-4 were targeted with replacement knockout constructs (13) in which the resistance cassette is flanked on both sides by Ϸ1 kb of gene-specific DNA. For PP2 knockout, a 2.1-kb genomic PCR product obtained with primers 5Ј-GGGAAGATGTCGACTCCCAAGAAG-3Ј (binding despite mismatches) and 5Ј-GCTGAGCTCATCCAT-GTC-3Ј was cloned into the EcoRV site of pBluescript II (KS Ϫ ) (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…1. Although the two desaturases (⌬ 6 -and ⌬ 5 -fatty acid desaturases) required for this pathway have been cloned recently from a number of different sources (7)(8)(9)(10)(11)(12)(13)(14), no genes have been characterized for the C2 elongation of the C18 PUFA. Biochemical characterization of mammalian elongation systems (most notably from liver microsomes) has indicated that the ''elongase'' actually consists of four enzyme activities, being made up of a condensing enzyme, a ␤-ketoreductase, a dehydrase, and an enoyl reductase (reviewed in ref.…”
mentioning
confidence: 99%